Mengaku Allah, Merupa Dalam Konteks: Tinjauan Historis terhadap Pengakuan Iman Gereja-gereja di Indonesia - Christanto Sema Rappan Paledung; Alfa Kristian Hia (IAKN Ambon, 2021)
This study is a historical description of the struggles of the churches in Indonesia on the relevance of the profession of faith to the context of their presence. This description focuses on some of these local churches in Indonesia, namely the Toraja Church, the Indonesian Christian Church, The Batak Christian Protestant Church, and the Javanese Christian Churches. These churches were born from the womb of zending which made them use the confession of faith from his predecessor church. However, the struggle with the context makes these churches have to formulate the confession of faith with awareness of the context. This paper explores these struggles using a historical approach. At the end, we will compare it with the Common Confession of Christian Faith formulated by the Communion of Churches in Indonesia. Our main argument is that the confession of faith of a church is a form of its struggle with the tradition in which it stands with the context of its presence.Abstrak Studi ini merupakan uraian historis mengenai pergulatan gereja-gereja di Indonesia terhadap relevansi pengakuan iman dengan konteks kehadirannya. Uraian ini berfokus kepada beberapa gereja lokal ini Indonesia, yakni Gereja Toraja, Gereja Kristen Indonesia, Huria Kristen Batak Protestan, dan Gereja-gereja Kristen Jawa. Gereja-gereja tersebut lahir dari rahim zending yang membuatnya menggunakan pengakuan iman dari gereja pendahulunya. Namun, pergulatan dengan konteksnya membuat gereja-gereja tersebut harus merumuskan pengakuan iman dengan kesadaran konteksnya. Studi ini menelusuri pergulatan tersebut dengan menggunakan pendekatan historis. Pada bagian akhir, kami akan membandingkannya dengan Pengakuan Bersama Iman Kristen yang dirumuskan Persekutuan Gereja-gereja di Indonesia. Argumen utama tulisan ini adalah bahwa pengakuan iman sebuah gereja merupakan wujud pergulatannya dengan tradisi di mana ia berpijak dengan konteks kehadirannya.